Dental fear in adults: a meta-analysis of behavioral interventions - Kvale G, Berggren U, Milgrom P. (Blackwell Synergy, 2004)
The aim of this meta-analytic and systematic quantitative approach is to examine the effects of behavioral interventions for dental anxiety and dental phobia.